Terapi Pijat Punggung Effleurage terhadap Intensitas Nyeri Akut Pasca Bedah Fraktur Tulang Panjang (Journal of Telenursing (JOTING), 2024)
This study examines the effect of effleurage back massage therapy on the intensity of acute pain after long bone fracture surgery. This research method is true experimental with a pretest-posttest control group design. The results showed a significant difference between the NSAID and NSAID groups with effleurage with a p-value